Peningkatan Pendapatan Desa Menuju Desa Mandiri Melalui Tata Kelola dan Sistem Pelaporan Keuangan Desa dan BUMDes - Savitri, Enni; Andreas, Andreas; Diyanto, Volta; Deliana, Evi; Hamzah, Amir (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
The issues with BUMDes and village funds include a lack of human resource competency, a vulnerability to financial mismanagement due to financial reports that don't follow government regulations, specifically SAK-ETAP, and the requirement for greater accountability from BUMDes and village funds. The governance of BUMDes and village funds truly needs innovation in digitalization, particularly when it comes to digitizing the financial reporting of these entities. The aim of the service is assistance in the operation of the innovation system for digitizing BUMDes financial reporting and village funds based on SAK-ETAP. Design and create a financial reporting system for BUMDes and village funds. The solution to this problem is to utilize financial and digital technology to speed up the financial management process of village and BUMDes funds. Problem identification and an evaluation of the actual and completed usage of village funds are two implementation strategies for resolving issues with managing BUMDes and village funds. interviews with residents and local officials to learn about the challenges encountered. arranging, establishing quantifiable and transparent management goals for the Village Fund. The creation of an integrated financial information system that is user-friendly is the outcome of the commitment to the usage of financial information systems. The advantages simplify record-keeping and financial management. Planning a budget and controlling financial risks. creation of a common, integrated financial reporting system for village funds and BUMDes.